Forming and consolidation of textile composites - Garcia-Gil, Rafael (2003)
Textile composite materials are of increasing interest not only in the automotive and aerospace industries, but also in other fields such as in the sporting and the marine sectors. However, textile composite materials are not always easy to form and consolidate, and defects such as voids, fibre displacements or wrinkling can inhibit the mechanical performance of the final component. Current tendencies in the textile composite industry focus on predicting such problems through the use of software packages for composite forming, such as PAM-FORM (ESI Software) and PATRAN Laminate Modeler (MSC. Software Ltd.). However, these packages are in their infancy, and so further work is needed to validate their results.